Using grounded theory as a method of inquiry: advantages and disadvantages - Hussein, Mohamed El; Hirst, Sandra; Salyers, Vince; Osuji, Joseph (My University, 2014)
There are many challenges and criticisms attached to the conduct of research, none the least of which is a notion that much of the research undertaken in professional disciplines such as nursing may not have clinical and/or practical relevance. While there are a plethora of qualitative research methods that individuals must consider when designing research studies, one method stands out - Grounded Theory (GT). Grounded theory was developed in the early 1960’s by Glaser and Strauss. With its theoretical orientation based in sociology, GT strives to understand and explain human behavior through inductive reasoning processes (Elliott & Lazenbatt, 2005). Because of its emphasis on the utilization of a variety of data sources that are grounded in particular contexts, GT provides a natural theoretical fit when designing nursing research studies. In this article, the authors provide an overview of GT and then describe the appropriateness, advantages, and disadvantages of applying it as part of the research design process. Additionally, the authors highlight the importance of taking a reflexive position to stay engaged while interacting with the data, and explore how to apply GT theory to particular research questions and studies. Finally, the strengths and limitations of this method of inquiry as applied to nursing research using a brief case study approach is presented.
Keywords: grounded theory; advantages; constructivist grounded theory